Water Management Mediated Chemical Kinetics of Soils Influencing Rice Growth - Patra, Prasanta Kumar (International Journal of Economic Plants, 2016)
The present field investigation was carried out to study the effect of water management mediated chemical kinetics of soil influencing Rice growth. Rice, the staple food of nearly half of the world population, is the most important crop of India occupying 23.3% of gross cropped area contributing 43% of total food grain production and 46% of total cereal production, continues to play vital role in the national food grain supply. Despite phenomenal increase in food grain production from 5l MT in 1950-51 to 264.38 Mt in 2013-2014. The System of Rice Intensification (SRI) formulated on certain core principles from soil chemistry and biology, rice physiology and genetics and the principles of sustainability with the possibility of adjusting the exact technical components based on the prevailing biophysical and socioeconomic realities of an area, is a niche –production method. Apart from “soil fertility management” through integrated use of organic and inorganic sources of plant nutrients, the system also results in saving significant amount of irrigation water in rice production. “Irrigation Water Management” is practiced in such a way that the soil is kept well drained rather than continuously flooded and saturated during the vegetative growth period. Water regime influences rice growth and yield by influencing different soil chemical and physic-chemical parameters which in turn influences the soil microbial community and their functions and thus turnover of nutrients. The effect is very much soil specific and no generalization can be made.